Public administration reform and the "new managerialism": a comparative assessment of a fundamental challenge confronting Canadian public administration - Wilson, V. Seymour (1996)
The "new managerialism" is becoming the new orthodoxy in public administration. It has challenged the classic assumptions about the nature of bureaucracy in democratic countries. However, it has not implied a great deal of serious debate. In Canada, it is challenging the model of constitutional bureaucracy around which public administration has been organized. Such a model involves two main principles: the ministerial Department and a neutral career public service. The former has meant that power flow in downward and responsibility and accountability upward (to the elected state authorities). The latter that, among other things, officials enjoy security of tenure in exchange for their willingness to serve governments of all partisan affiliations with equal loyalty and effectiveness. The new managerialism challenges both principles since it proposes to diffuse authority both horizontally and vertically, make accountability run downward to "clients" and be more capable to substitute personnel according to the needs of the moment. Since the new managerialism involves serious risks, the author ends up asking whether these two contending paradigms can or should be reconcilied, and warning not to overlook the past histories of Canadian and Western administrative and political institutions. - Reproduced
Keywords: Public administration - Canada; Managers - Canada; Public Administration